PENERAPAN ARSITEKTUR METAFORA PADA PERANCANGAN MUSLIM FASHION CENTER DI JAKARTA SELATAN - Putri, Ananda Amelia; Putri, Ananda Amelia; Endangsih, Tri (MAESTRO, 2021)
The development of the era affects the development of fashion from time to time. Fashion is synonymous with a person's lifestyle, because fashion is a style that refers to a way of dressing that is trending or popular in society. The development of Muslim fashion is currently growing very rapidly, it can be seen from the increasing number of Muslim women who wear the hijab. Nowadays hijab is increasingly recognized and loved by various age groups, this is what makes Muslim fashion continue to grow. South Jakarta has the potential as a business center, especially in the fashion sector. The Muslim Fashion Center is designed as a place for work, entertainment, and shopping for designers and Muslim fashion enthusiasts to express their creativity and increase knowledge about the Muslim fashion world. In this design using Metaphoric Architecture, to create a harmonious and attractive building that makes the building more expressive and characterized by the function of the building as a Muslim Fashion Center.